Characteristics and Outcomes of Women Developing Heart Failure After Early Stage Breast Cancer Chemotherapy: A Population-Based Matched Cohort Study. (July 2021) - Abdel-Qadir, Husam; Tai, Felicia; Croxford, Ruth; Austin, Peter C.; Amir, Eitan; Calvillo-Argüelles, Oscar; Ross, Heather; Lee, Douglas S.; Thavendiranathan, Paaladinesh
Abstract : Background: The prognosis of heart failure (HF) after early stage breast cancer (EBC) treatment with anthracyclines or trastuzumab is not well-characterized. Methods: Using administrative databases, women diagnosed with HF after receiving anthracyclines or trastuzumab for EBC in Ontario during 2007 to 2017 (the EBC-HF cohort) were categorized by cardiotoxic exposure (anthracycline alone, trastuzumab alone, sequential therapy with both agents) and matched on age with ⩽3 cancer-free HF controls to compare baseline characteristics. To study prognosis after HF onset, we conducted a second match on age plus important HF prognostic factors. The cumulative incidence function was used to describe risk of hospitalization or emergency department visits (hospital presentations) for HF and cardiovascular death. Results: A total of 804 women with EBC developed HF after anthracyclines (n=312), trastuzumab (n=112), or sequential therapy (n=380); they had significantly fewer comorbidities than 2411 age-matched HF controls. After the second match, the anthracycline-HF cohort had a similar 5-year incidence of HF hospital presentations (16.5% [95% CI, 12.0%–21.7%]) as controls (17.1% [95% CI, 14.4%–20.1%]); the 5-year incidence was lower than matched controls for the trastuzumab-HF (9.7% [95% CI, 4.7%–16.9%]; controls 16.4% [95% CI, 12.1%–21.3%]; P =0.03) and sequential-HF cohorts (2.7% [95% CI, 1.4%–4.8%]; controls 10.8% [95% CI, 8.9%–13.0%]; P <0.001). At 5 years, the incidence of cardiovascular death was 2.9% (95% CI, 1.2%–5.9%) in the anthracycline-HF cohort vs. 9.5% (95% CI, 6.9%–12.6%) in controls, and 1.7% (0.6%–3.7%) for women developing HF after trastuzumab vs. 4.3% (95% CI, 3.1–5.8%) for controls. Conclusions: Women developing HF after cardiotoxic EBC chemotherapy have fewer comorbidities than cancer-free women with HF; trastuzumab-treated women who develop HF have better prognosis than matched HF controls. Abstract : Supplemental Digital Content is available in the text.